2022
DOI: 10.1177/15459683221092995
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Cerebellar Intermittent Theta Burst Stimulation Combined With Swallowing Speech Therapy for Dysphagia After Stroke: A Randomized, Double-Blind, Sham-Controlled, Clinical Trial

Abstract: Background: Previous studies have found that high-frequency repetitive transcranial magnetic stimulation (rTMS) of the cerebellar hemisphere could improve swallowing function, but whether intermittent theta burst stimulation (iTBS), which has similar excitatory effect and higher efficiency, can also improve swallowing function for dysphagia after stroke remains unclear. Objective: This trial aimed to explore the efficacy and safety of bilateral cerebellar transcranial magnetic stimulation with iTBS for dysphag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 53 publications
0
39
0
1
Order By: Relevance
“…However, 1200-pulse iTBS could attenuate the increase in excitability caused by 600-pulse iTBS ( 24 ). For clinical research, several RCTs have been used to evaluate the effects of iTBS on language function, cognitive function, and swallowing function after stroke ( 25 27 ). Previous studies have shown that iTBS can reduce aphasia and improve motor function in stroke patients ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, 1200-pulse iTBS could attenuate the increase in excitability caused by 600-pulse iTBS ( 24 ). For clinical research, several RCTs have been used to evaluate the effects of iTBS on language function, cognitive function, and swallowing function after stroke ( 25 27 ). Previous studies have shown that iTBS can reduce aphasia and improve motor function in stroke patients ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…During iTBS, a 2 s train was followed by an 8 s intermission; this pattern was repeated 20 times for approximately 190 s (600 pulses). The iTBS was delivered at 100% resting motor threshold (rMT) ( Rao et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…This method has led to some achievements in the research of neural mechanisms in the field of swallowing ( Ruan et al, 2017 ). Cerebellar iTBS has been shown to improve swallowing function in poststroke patients with dysphagia ( Rao et al, 2022 ). Furthermore, the fractional amplitude of low-frequency fluctuation (fALFF) approach has high sensitivity and specificity in detecting spontaneous brain activities.…”
Section: Introductionmentioning
confidence: 99%
“…Applications regarding cerebellar TMS in cerebral stroke rehabilitation according to current literature concern dysphagia, gait-balance, and limb spasticity as outcomes of interest. Both rTMS and TBS have been studied but there is a prominent application of TBS, the main reason being that it can induce long-lasting cortical excitability with both lower stimulation intensity and training duration [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study by Rao et al (2022) investigated an iTBS protocol [ 39 ] in 70 patients with endoscopically confirmed dysphagia. A clinically significant difference in improvement was recorded in favor of the real-iTBS group, with the degree of improvement approaching clinically the difference between nasogastric tube and oral feeding, or parenteral fluid supplementation vs. oral fluid intake [ 33 ].…”
Section: Resultsmentioning
confidence: 99%